The Effect of Hedonic Motivation and Positive Affect on Impulsive Buying Behavior Mediated by Shopping Lifestyle - Rosa Nur Maulia Saputra; Rini Kuswati (Eduvest - Journal of Universal Studies, 2024)
The rapid advancement of technology has significantly influenced consumer behavior, leading to increased impulsive buying in e-commerce platforms. This study explores the impact of hedonic motivation and positive affect on impulsive buying behavior, mediated by shopping lifestyle. A quantitative research method was used, involving 160 respondents from Surakarta who actively use the Shopee application. Data were analyzed using Partial Least Square (PLS) with SmartPLS software. The results show that hedonic motivation does not have a direct significant effect on impulsive buying; however, positive affect significantly influences impulsive purchases. Additionally, hedonic motivation does not significantly affect shopping lifestyle, whereas positive affect does. Shopping lifestyle was found to have a significant effect on impulsive buying, but it does not mediate the relationship between hedonic motivation and impulsive buying or between positive affect and impulsive buying. These findings suggest that positive emotional experiences during shopping play a crucial role in driving impulse purchases, while hedonic motivations may require stronger mediating factors to influence impulsive buying behavior.